FAR1 and FAR2 regulate the expression of genes associated with lipid metabolism in the rice blast fungus Magnaporthe oryzae - Yusof, Mohammad Termizi; Kershaw, Michael J.; Soanes, Darren M.; Talbot, Nicholas J. (Public Library of Science, 2014)
The rice blast fungus Magnaporthe oryzae causes plant disease via specialised infection structures called appressoria. These dome-shaped cells are able to generate enormous internal pressure, which enables penetration of rice tissue by invasive hyphae. Previous studies have shown that mobilisation of lipid bodies and subsequent lipid metabolism are essential pre-requisites for successful appressorium-mediated plant infection, which requires autophagic recycling of the contents of germinated spores and germ tubes to the developing appressorium. Here, we set out to identify putative regulators of lipid metabolism in the rice blast fungus. We report the identification of FAR1 and FAR2, which encode highly conserved members of the Zn2-Cys6 family of transcriptional regulators. We generated Δfar1, Δfar2 and Δfar1Δfar2 double mutants in M. oryzae and show that these deletion mutants are deficient in growth on long chain fatty acids. In addition, Δfar2 mutants are also unable to grow on acetate and short chain fatty acids. FAR1 and FAR2 are necessary for differential expression of genes involved in fatty acid β-oxidation, acetyl-CoA translocation, peroxisomal biogenesis, and the glyoxylate cycle in response to the presence of lipids. Furthermore, FAR2 is necessary for expression of genes associated with acetyl-CoA synthesis. Interestingly, Δfar1, Δfar2 and Δfar1Δfar2 mutants show no observable delay or reduction in lipid body mobilisation during plant infection, suggesting that these transcriptional regulators control lipid substrate utilization by the fungus but not the mobilisation of intracellular lipid reserves during infection-related morphogenesis.